Anlotinib Combined with S-1 in Third- or Later-Line Stage IV Non-Small Cell Lung Cancer Treatment: A Phase II Clinical Trial. (13th September 2021) - Xiang, Miao; Yang, Xiyue; Ren, Surong; Du, Huan; Geng, Lidan; Yuan, Li; Wen, Yixue; Lin, Binwei; Li, Jie; Zhang, Yu; Feng, Gang; Du, Xiaobo
Abstract : Lessons Learned : The combination of anlotinib and S-1 exhibited good antitumor activity in third- or later-line treatment for stage IV non-small cell lung cancer (NSCLC). Combination therapy of anlotinib with S-1 has manageable toxicities in patients with NSCLC. Background: This study aimed to evaluate the efficacy and safety of anlotinib combined with S-1 as a third- or later-line treatment for patients with stage IV non-small cell lung cancer (NSCLC). Anlotinib was approved in 2018 by the Chinese Food and Drug Administration (FDA) as a third-line treatment for patients with refractory advanced NSCLC and is under study in the U.S. and Europe. Methods: Simon's phase II clinical trial design with an α error of 5% and a power β of 80% was used, anticipating a 10% objective response rate (ORR) of anlotinib and a 30% ORR of anlotinib combined with S-1; the required sample size was 29. A total of 29 patients were enrolled in the clinical trial. Patients were treated with anlotinib plus S-1 over a 21-day treatment course until disease progression or unacceptable toxic effects. If the efficacy was assessed as stable disease, partial response, or complete response after six cycles, anlotinib was maintained until disease progression or death. The primary endpoint was the objective response rate. Somatic mutations were not required for study enrollment. Results: The median follow-up time was 11.1 months. Objective responses were observed in 11 of 29 (37.9%) patients making up the intention-to-treat population, which reached the target primary endpoint of 30% ORR. The median overall and progression-free survival were 16.7 and 5.8 months, respectively. The most common grade 3 adverse events (AEs) were gastrointestinal, including nausea, vomiting and diarrhea, fatigue, and hypertension. No grade 4 treatment-related AEs or treatment-related deaths occurred. Conclusion: The combination of anlotinib with S-1 in the third- or later-line treatment of stage IV NSCLC shows promising antitumor activity and manageable toxicity in patients with NSCLC; phase III trials will be planned in the future.